Efficacy and safety of tacrolimus monotherapy versus tacrolimus-corticosteroid combination therapy for idiopathic membranous nephropathy: A meta-analysis. Issue 51 (23rd December 2021) - Gong, Lifeng; Xu, Min; Xu, Wei; Tang, Weigang; Lu, Jingkui; Jiang, Wei; Xie, Fengyan; Ding, Liping; Qian, Xiaoli
Abstract: Objective: The objective of this meta-analysis was to compare the efficacy and safety of tacrolimus (TAC) monotherapy versus TAC-corticosteroid combination therapy in idiopathic membranous nephropathy (IMN) patients. Methods: Databases including PubMed, Embase, the Cochrane Library, China National Knowledge Infrastructure, and Wanfang database were searched from inception to January 10, 2021. Eligible studies comparing TAC monotherapy and TAC-corticosteroid combination therapy in IMN patients were included. Data were analysed using Review Manager Version 5.3. Results: Seven studies were included in the meta-analysis. One randomized controlled trial and six cohort studies involving 372 patients were identified. Compared with TAC monotherapy, TAC-corticosteroid had a higher total remission at the sixth month (odd ratio (OR) 0.49, 95% confidence interval (CI) 0.31–0.78, P < .01). The two therapy regimens had similar complete remission rates (OR 0.79, 95% CI 0.43–1.48, P = .47) at the sixth month and similar relapse rates (OR 1.44, 95% CI 0.70–2.92, P = .32). TAC-corticosteroid combination therapy had a higher incidence of infection (OR 0.38, 95% CI 0.18–0.81, P = .01). The two therapy regimens had similar incidences of gastrointestinal symptoms (OR 0.96, 95% CI 0.34–2.70, P = .93), abnormal aminotransferase (OR 0.90, 95% CI 0.34–2.38, P = .84), and glucose intolerance (OR 0.58, 95% CI 0.32–1.07, P = .08). Conclusion: TAC-corticosteroid combination therapy had a higher total remission rate at the sixth month but had a higher incidence of infection than TAC monotherapy in the treatment of IMN. The two therapeutic regimens had similar relapse rates.